2013
DOI: 10.1097/rlu.0b013e31829b2686
|View full text |Cite
|
Sign up to set email alerts
|

Is 18F-FDG PET/CT Useful for Distinguishing Between Primary Thyroid Lymphoma and Chronic Thyroiditis?

Abstract: The SUV(max) was significantly higher and the CT density was significantly lower in PTL as compared with those in chronic thyroiditis. Thus, (18)F-FDG PET/CT may be useful for distinguishing between PTL and chronic thyroiditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In a recent 18 F-FDG PET/ CT study, malignant lymph nodes were reported to display higher HU compared to the benign ones in lung cancer [22]. In another 18 F-FDG PET/CT study, the CT density in primary thyroid lymphoma was found to be lower than that measured in chronic thyroiditis [23]. All the above mentioned studies demonstrate that CT density measurements are irreplaceable components of 18 F-FDG PET/CT imaging and the threshold or mean HU values differ significantly from one malignant tumor type to the other.…”
Section: Discussionmentioning
confidence: 88%
“…In a recent 18 F-FDG PET/ CT study, malignant lymph nodes were reported to display higher HU compared to the benign ones in lung cancer [22]. In another 18 F-FDG PET/CT study, the CT density in primary thyroid lymphoma was found to be lower than that measured in chronic thyroiditis [23]. All the above mentioned studies demonstrate that CT density measurements are irreplaceable components of 18 F-FDG PET/CT imaging and the threshold or mean HU values differ significantly from one malignant tumor type to the other.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have suggested that FDG-PET has superior accuracy in staging of lymphoma compared to computed tomography or magnetic resonance imaging (25). It may provide more accurate staging in thyroid lymphoma (26,27); therefore, some patients in our study might be diagnosed as having more advanced clinical stage lymphoma. Future studies will allow a proper interpretation.…”
Section: Discussionmentioning
confidence: 89%
“…However, a recent study in a large patient group revealed that SUV max was significantly higher and CT density was lower in primary thyroid lymphoma as compared to chronic thyroiditis. The authors have thus suggested that 18 F-FDG PET/CT may be helpful in distinguishing primary thyroid lymphoma from chronic thyroiditis (45). Similarly, a large series of thyroid lymphoma from a single center have been recently reported.…”
Section: Thyroid Lymphomamentioning
confidence: 99%